(untitled) (Indian Journal of Chemistry (IJC), 2024)
This study explores the DNA-binding and DNA-cleaving properties of two newly synthesized oxime derivative ligands and their complexes with Cu(II) and Ni(II) metal ions. Sodium salts of these compounds were prepared to ensure water solubility. The structures of the ligands and complexes were elucidated through various analytical techniques, including 1H-NMR, FT-IR, TGA, UV-vis, SEM-EDS, and XRD analyses. The results reveal that these compounds interact with DNA without significantly altering its structure. They primarily bind to DNA grooves, particularly major grooves. The study determined that the optimal concentration for these interactions is 75 µM. Viscometry studies show that these compounds do not substantially change DNA viscosity, suggesting groove binding as their mode of interaction without major structural modifications to DNA. Gel electrophoresis, an effective tool for elucidating DNA cleavage mechanisms, indicates that DNA cleavage activity persists in the presence of radical scavengers, although it is reduced, especially in compounds known to bind to DNA grooves. In broader terms, complexes with Ni(II) exhibit higher DNA interaction activity than Cu(II) for both ligands. Among the ligands themselves, H2L1 demonstrates higher activity than H3L2. In conclusion, this research reveals that these compounds interact with DNA, primarily through groove binding, with minimal impact on DNA structure. This has implications for biomedical and pharmaceutical applications, highlighting these compounds’ potential in these fields.